2016
DOI: 10.5812/pedinfect.37629
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Diffusely Adherent Escherichia coli Strains Associated with Diarrhea in Shiraz, Iran

Abstract: Background: Diarrhea continues to be one of the most common causes of morbidity and mortality among children in developing countries. Recently, some studies have implicated diffusely adherent Escherichia coli (DAEC) strains as a cause of diarrhea. The clinical manifestations of diarrhea caused by DAEC strains may include watery or bloody diarrhea, abdominal pain, dehydration, and fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…DAEC was found more often in isolates from diarrheic isolates (29/35; 82.8%) as compared to isolates from UTI isolates (6/35; 17.1%). The prevalence of DAEC ranged from about 8% (Shiraz)[ 27 ] to 9% (Tehran and Sanandaj)[ 16 ] in Iran [ Appendix 1 and Figure 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…DAEC was found more often in isolates from diarrheic isolates (29/35; 82.8%) as compared to isolates from UTI isolates (6/35; 17.1%). The prevalence of DAEC ranged from about 8% (Shiraz)[ 27 ] to 9% (Tehran and Sanandaj)[ 16 ] in Iran [ Appendix 1 and Figure 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pathogenic E. coli is divided into two subgroups according to its predilection, namely, diarrheagenic E. coli (DEC) [54,58], which is pathogenic in the digestive tract, and ExPEC [26,59], which causes systemic infections [50]. Diarrheagenic E. coli is found in the intestinal tracts of both humans and animals and is classified into eight sub-pathotypes, including EPEC [60,61], enterotoxigenic E. coli (ETEC) [62][63][64], enterohemorrhagic E. coli (EHEC) [65][66][67], enteroinvasive E. coli (EIEC) [68][69][70][71], diffusely adherent E. coli [72][73][74][75][76], enteroaggregative E. coli (EAEC) [75,[77][78][79][80][81], adherent invasive E. coli [82][83][84][85], and Stx-producing EAEC [65,77,81,86]. Diarrheagenic E. coli is transmitted through food or water contaminated with animal or human feces and causes gastroenteritis and diarrhea.…”
Section: Avian Pathogenic E Colimentioning
confidence: 99%
“…Previous studies have shown that developed multiplex-PCR (m-PCR) was rapid and ideal for the identification of specific genes that encoded to specific virulence factors. The target genes include: aat2 (CVD432), AggR, eae, ipaH, stx1, stx2, bfpA, elt, estA1, estA2-4, and daaD [8,9]. The aat2 encoded to dispersin protein involved in aggregation, AggR regular the gene expression to adherence factors [10,11].…”
Section: Introductionmentioning
confidence: 99%